Genetic algorithm-based active noise control systems - simulations using Internet - Makarewicz, G. (Archives of Acoustics, 2004)
The application of genetic algorithm in Active Noise Control (ANC) systems is described here. Advantages and disadvantages of genetic algorithm-based ANC systems are discussed. Two types of genetic algorithm: binary and continuous parameter, in the context of ANC systems, are analyzed. The software for simulation of ANC systems based on gradient and genetic algorithms is described. The software consists of modules which represent functional elements of ANC systems. These modules can be easily implemented into programs for simulation of specific structures of ANC systems. The software was written in JAVA and simulations can be performed using Internet. Some results of the simulations are described. The software is currently available on www.anc.pl.